The Effect of COVID-19 Pandemic News Coverage on New Normal Tourism in Indonesia - Morissan, Morissan (Journal of Contemporary Issues in Media & Communication (JCIMC), 2022)
Along with the recent decline in the number of Covid-19 cases in Indonesia, people's mobility has begun to increase, including traveling. This study highlights the effect of Covid-19 pandemic news coverage on the public's intention to travel during the pandemic by implementing health protocols, known as new normal tourism, as a behavior to protect health based on individual perceptions of their risk of being infected with Covid-19. Referring to the frameworks of the Health Belief Model and Theory of Planned Behavior, this study examines the effect of COVID-19 risk perception on behavioral intention towards new normal tourism. An online questionnaire using Google Form was distributed in Jakarta from April 18 – 21, 2021, and data from 483 respondents were used for analysis. The findings show that affective risk perception is a significant predictor of attitude, while cognitive risk perception has a positive influence on subjective norms. Despite the fact that both cognitive and affective risk perceptions have a considerable impact on behavioral intention, affective risk perception has a negative influence, which contradicts the initial hypothesis. Subjective norms mediated the relationship between cognitive perception and behavioral intention, whereas attitude was found to be a significant mediator between affective risk perception and behavioral intention. The hypothesized relationships were partially mediated by gender and marital status. This study has important and insightful implications for tourism practitioners who would be asked to prepare the post-corona field for a new normal following the pandemic.